Knowledge, Beliefs, and Attitudes of Junior High School Students in Palembang Towards Climate Change Issues - Chairunnisa Chairunnisa; Ida Sriyanti; Meilinda Meilinda; Nyimas Aisyah; Ismet Ismet (Postgraduate, University of Mataram, 2022)
Climate change is one of the most pressing problems at all levels of government around the world, threatening the global economy as well as the very existence of planet earth. This study aimed to examine the knowledge, beliefs, and attitudes of Palembang City junior high school students on climate change. The research method used is qualitative research. Data were obtained through questionnaires. There were 744 junior high pupils in the study, ranging in age from 11 to 16. The results showed that students' initial knowledge about climate change was 65.73%, students' beliefs about the causes and impacts of climate change were 65.50%, and students' attitudes to mitigating climate change were 69.50%. Students' beliefs about climate change opinions are also influenced by the contribution of the general media by 34.50%.